Avaliação do condicionamento de jogadoras amadoras de futsal indígenas da associação dos povos indígenas estudantes na Universidade Federal do Pará (APYEUFPA) e de futebol de campo das indígenas da etnia Tembé - COSTA, Erick Sander Tavares (2022)
Introduction: The research was structured based on a study with the UFPA indigenous female players in the futsal modality, and also on the Tembé ethnic female soccer players. Objective: To assess the fitness level of the Association of Indigenous Peoples Students of the Federal University of Pará (APYEUFPA) Indigenous Futsal Team and the Tembé Ethnic Soccer Team. ” Methods: 12 university indigenous female players from the APYEUFPA, with an average age of 25.8 years ( 6.1), and body mass 61.9 Kg ( 3, 27) and height of 1.56 m ( 0.04). And 24 Tembé players from Frasqueira village, with an average age of 17.8 years ( 3.8), body mass of 54.9 Kg ( 1.75) and height of 1.54 m ( 0, 04). The athletes were submitted to tests to evaluate the physical conditioning. Comparison between groups was performed by one-way ANOVA for each item (p <0.05). Results: Statistical analysis showed that there were differences between the two groups in all tests performed. Conclusion: The results compared between the groups were different, but when compared with the available literature showed that the conditioning level of indigenous players is below the level. of futsal and soccer athletes.